Factors impacting time to genetic diagnosis for children with epilepsy - Megan Rimmasch; Carey A. Wilson; Nephi A. Walton; Kelly Huynh; Joshua L. Bonkowsky; Rachel Palmquist (Epilepsia Open)
Abstract Molecular diagnosis for pediatric epilepsy patients can impact treatment and health supervision recommendations. However, there is little known about factors affecting the time to receive a diagnosis. Our objective was to characterize factors affecting the time from first seizure to molecular diagnosis in children with epilepsy. A retrospective, population‐based review was used to analyze data from pediatric patients with a genetic etiology for epilepsy over a 5 year period. A subgroup of patients with seizure onset after 2016 was evaluated for recent trends. We identified 119 patients in the main cohort and 62 in a more recent (contemporaneous) subgroup. Sex, race, and ethnicity were not significantly associated with time to molecular diagnosis. A greater number of hospitalizations was associated with a shorter time to diagnosis (p < 0.001). Developmental delay was associated with a longer time to diagnosis (p = 0.002). We found no association for time to diagnosis with a diagnosis of autism, utilization of free genetic testing, or epilepsy type. In the recent subgroup analysis, commercial insurance was associated with decreased time to diagnosis (p = 0.02). Developmental delay, public insurance, or patients in the outpatient setting had longer times to molecular diagnosis. These findings suggest that there may be opportunities to implement interventions aimed at accelerating the provision of genetic testing in pediatric epilepsy. Plain Language Summary Genetic diagnosis for pediatric epilepsy patients can impact treatment and care. This study looked at factors that affect how long it takes a pediatric epilepsy patient to receive a genetic diagnosis. We found that sex, race and ethnicity, epilepsy type, and whether the patient had autism did not affect how long it took the patient to receive a diagnosis. However, we found that patients with developmental delay, fewer hospitalizations, and public insurance took a longer time to receive a diagnosis. Our findings suggest potential strategies for reducing the time to receive a genetic diagnosis.